ARHGEF28 gene exon 6/intron 6 junction mutations in Chinese amyotrophic lateral sclerosis cohort. Issue 3 (1st June 2014) - Ma, Yan; Tang, Lu; Chen, Lu; Zhang, Bin; Deng, Pan; Wang, Jingran; Yang, Yi; Liu, Rong; Yang, Yan; Ye, Shan; Liu, Xiaolu; Zhang, Huagang; et al.
Abstract: It was reported that the intron 6, + 1 del G (GT>TT) mutation of the ARHGEF28 gene generates a shortened protein that might be related to amyotrophic lateral sclerosis (ALS). We sequenced this mutation in 25 familial ALS (FALS), 357 sporadic ALS (SALS) patients, and 442 healthy control subjects. We found just two SALS patients exhibited the mutation so that the incidence of this mutation was 0.52% (2/382) of all the ALS patients. The clinical features of the mutation-positive patients were quite different from the case reported in a previous study. These characteristics differed in terms of gender, site of onset, cognitive function, and family history.